Mechanical Properties of Epoxy Composites Containing Carbon Black and Graphene - Othman, R. N.; Rahman, I. A.; Faidzi, M. K.; Ku Ahmad, K. Z. (International Journal of Integrated Engineering, 2020)
Epoxy composite has been widely used in various industrial applications due to its high strength. Nevertheless, its high strength causes it to fracture easily. Fillers are often added to improve its fracture toughness and other properties. In this work, epoxy composites containing carbon black (CB) and graphene have been synthesized to assess their mechanical properties. Series of analysis have been performed on composites containing single filler (CB or graphene) of various loadings to evaluate the values of Young’s Modulus, yield strength, and KIC. The results demonstrate an improvement in Young’s Modulus, yield strength, and KIC values by adding different carbon fillers, compared to neat epoxy. Based on these results, composites containing dual fillers are fabricated to understand the resultant synergistic effects. The hy-brid fillers show an increment in both fracture toughness and yield strength test for the epoxy composite with an optimum improvement at (3.0 wt.% CB + 0.1 wt.% Graphene) loading which is an increase of 256% in the values of Young’s Modulus, compared to neat epoxy. The addition of carbon fillers enhances the mechanical properties of epoxy composites, with dual fillers demonstrate the highest improve-ment, which could be due to the improvement in the dispersion degree.